2018
DOI: 10.1038/nrn.2017.168
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and the maintenance of elevated body weight

Abstract: Obesity represents the single most important risk factor for early disability and death in developed societies, and the incidence of obesity remains at staggering levels. CNS systems that modulate energy intake and expenditure in response to changes in body energy stores serve to maintain constant body adiposity; the adipocyte-derived hormone leptin and its receptor (LEPR) represent crucial regulators of these systems. As in the case of insulin resistance, a variety of mechanisms (including feedback inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
219
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(228 citation statements)
references
References 101 publications
6
219
0
3
Order By: Relevance
“…The increased basal levels of STAT3 phosphorylation, displayed by DIO rodents in hypothalamic nuclei and especially in the ARC, were proposed to support this notion of increased endogenous leptin-mediated STAT3 signaling in response to elevated endogenous leptin [78]. The interesting observation of augmented basal STAT3 activity in DIO could also result from potential ligand independent activity of ObR that would be sensitive to the blockage by a receptor antagonist.…”
Section: The Debate On Leptin Resistancementioning
confidence: 73%
See 1 more Smart Citation
“…The increased basal levels of STAT3 phosphorylation, displayed by DIO rodents in hypothalamic nuclei and especially in the ARC, were proposed to support this notion of increased endogenous leptin-mediated STAT3 signaling in response to elevated endogenous leptin [78]. The interesting observation of augmented basal STAT3 activity in DIO could also result from potential ligand independent activity of ObR that would be sensitive to the blockage by a receptor antagonist.…”
Section: The Debate On Leptin Resistancementioning
confidence: 73%
“…Indeed, since ObRb displays low neuronal expression and transient or weak signaling, the detection of its downstream signaling pathways is difficult in vivo, with the exception of pSTAT3 which is considered to be the canonical marker for ObRb activation [78]. However, the leptin signaling pathways can be differentially impacted upon HFD, as we observed in our recent study with the striking phenotype of Endo1-silenced mice [77], and as observed by others [83] and discussed below.…”
Section: The Debate On Leptin Resistancementioning
confidence: 99%
“…Increased adiposity, a key hallmark of obesity, is associated with elevated levels of circulating leptin . Leptin, an adipocyte‐derived cytokine, binds to leptin receptors in several brain areas to initiate signalling cascades via phosphorylation of signal transducer and activator of transcript 3 (STAT3) . Within the arcuate nucleus of the hypothalamus (ARC), neurones expressing the anorectic transcript proopiomelanocortin ( Pomc ) and neurones expressing the orexigenic transcripts agouti‐related peptide ( Agrp ) and neuropeptide Y ( Npy ) are oppositely modulated by leptin to regulate feeding behaviour, glucose homeostasis and energy expenditure .…”
Section: Effects Of Fc‐hfhs On Physiologymentioning
confidence: 99%
“…Increased adiposity is associated with increased circulating leptin levels, leading to suppressed feeding and increased energy expenditure. Conversely, a fall in circulating levels signifies energy deficit, promoting feeding and energy conservation . In mice, genetic loss of function of either leptin ( ob/ob ) or the leptin receptor ( db/db ) genes leads to hyperphagia and major obesity.…”
Section: Introductionmentioning
confidence: 99%